The last kiss [videorecording (DVD)] - Goldwyn, Tony; Braff, Zach, 1975-; Barrett, Jacinda; Affleck, Casey, 1975-; Muccino, Gabriele (Paramount Pictures, 2006)
Michael and Jenna have been a couple for three years. At dinner one night, Jenna's parents, Anna and Stephen, announce that they are having a baby. Jenna is overjoyed, but everyone else has mixed emotions. At a wedding the next day, Jenna and Michael meet up with friends Chris, who is tired of his wife telling him how bad he is as she deals with their whiny baby; Izzy who is taking the break-up of his most current relationship badly and does not react well when his former girlfriend shows up at the wedding; and Kenny who is a dedicated bachelor and prefers to keep it that way. Then Michael meets Kim, a forward young college student. Michael is beginning to feel that his "entire life has the feeling it has all been planned out" and Kim provides a welcome distraction.